2021
DOI: 10.1063/5.0040172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of side chain modifications in imidazolium ionic liquids on the properties of the electrical double layer at a molybdenum disulfide electrode

Abstract: Knowledge of how the molecular structures of ionic liquids (ILs) affect their properties at electrified interfaces is key towards the rational design of ILs for electric applications. Polarizable molecular dynamics simulations were performed to investigate the structural, electrical and dynamic properties of electric double layers (EDLs) formed by imidazolium dicyanamide ([ImX1][DCA]) at the interface with molybdenum disulfide electrode. The effect of side chain of imidazolium on the properties of EDLs was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 76 publications
(96 reference statements)
3
24
0
Order By: Relevance
“…Integration was done using the velocity Verlet algorithm with the temperature-grouped Dual–Nosé–Hoover thermostat as described in ref. 40 and 41, which implements an additional temperature group for the center-of-mass translations. The non-Drude particles were kept at 300 K and the Drudes at 1 K. The collision frequency was set to 10 ps −1 for the atoms and to 200 ps −1 for the Drude particles.…”
Section: Methodsmentioning
confidence: 99%
“…Integration was done using the velocity Verlet algorithm with the temperature-grouped Dual–Nosé–Hoover thermostat as described in ref. 40 and 41, which implements an additional temperature group for the center-of-mass translations. The non-Drude particles were kept at 300 K and the Drudes at 1 K. The collision frequency was set to 10 ps −1 for the atoms and to 200 ps −1 for the Drude particles.…”
Section: Methodsmentioning
confidence: 99%
“…2 For example, the processes of energy storage and release are closely related to the EDL structure in IL-based supercapacitors, which is composed of an inner tightly bound ion layer and an outer loose layer with alternating cations and anions. [3][4][5][6][7] The formation of either a multilayer alternating cation and an anion structure or a distinctive dense counterion monolayer in ILs across the longitudinal direction to the surface has been confirmed by both experimental 4,[6][7][8][9][10][11] and theoretical [12][13][14][15][16] studies and suggested to play a crucial role in the capacitive performance at IL-electrode interfaces. 16,17 The capacitance of ILs at the electrode surface is reported to be determined by, and reflects, the microstructural changes within the innermost region of the EDL.…”
Section: Introductionmentioning
confidence: 85%
“…[3][4][5][6][7] The formation of either a multilayer alternating cation and an anion structure or a distinctive dense counterion monolayer in ILs across the longitudinal direction to the surface has been confirmed by both experimental 4,[6][7][8][9][10][11] and theoretical [12][13][14][15][16] studies and suggested to play a crucial role in the capacitive performance at IL-electrode interfaces. 16,17 The capacitance of ILs at the electrode surface is reported to be determined by, and reflects, the microstructural changes within the innermost region of the EDL. 14 Generally, most cations and anions prefer to form 'neutral aggregates', i.e., the cation-anion alternating structure in the EDL because the ion distribution is mainly dominated by coulombic interactions.…”
Section: Introductionmentioning
confidence: 85%
“…The purple points are the image charges. Reproduced with permission from ref . Copyright 2021 AIP Publishing.…”
Section: Molecular-scale Simulation Methods For Capacitorsmentioning
confidence: 99%